Composite powder for battery diaphragm, preparation method of composite powder, battery diaphragm, battery and electrochemical device

By using composite powder covering the polymer layer in the lithium-ion battery separator, the problem of transition metal ions dissolution in the inorganic powder is solved, the wetting property of the battery separator and the stability of the battery capacity are improved, and the safety of the electrochemical device is enhanced.

CN119864597APending Publication Date: 2025-04-22NANJING NORMAL UNIV TAIZHOU COLLEGE
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411950899.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Transition metal ions in the inorganic powder in the existing lithium-ion battery separator are easily dissolved under high voltage and high temperature conditions, resulting in sharp attenuation of battery capacity and safety issues. The existing water washing method can only clean ions on the surface of the powder particles, and the internal ions will still migrate during use.

Method used

The composite powder is formed by covering the polymer layer on the surface of alumina or boehmite and adopting a specific preparation method, including reaction and polycondensation under water bath heating conditions, to form a battery separator ceramic coating with excellent properties.

Benefits of technology

The precipitation of transition metal ions is reduced, the wetting properties of the battery separator and electrolyte are improved, the attenuation of battery capacity is delayed, and the safety of electrochemical devices is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864597A_ABST
    Figure CN119864597A_ABST
Patent Text Reader

Abstract

The invention discloses composite powder for a battery diaphragm and a preparation method of the composite powder, the battery diaphragm, a battery and an electrochemical device, and belongs to the technical field of battery materials, the composite powder comprises inorganic powder and a polymer layer coating the surface of inorganic powder particles, the inorganic powder is selected from one or more of aluminum oxide and boehmite, and the polymer layer is selected from one or more of aluminum oxide and boehmite. The polymer layer comprises one or more of polymethyl methacrylate (PMMA), an organosilicon polymer, polyphenyl ether (PPO) and polyethylene naphthalate (PEN), and the mass of the polymer layer accounts for 1-10 wt% of the mass of the composite powder. The composite powder for the ceramic coating of the battery diaphragm provided by the invention is small in ion dissolution amount, and the battery diaphragm prepared from the composite powder and an electrolyte have relatively good wettability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a composite powder for a battery separator and a preparation method thereof, a battery separator, a battery, and an electrochemical device. Background Art

[0002] Lithium-ion batteries are usually composed of a lithium-containing transition metal oxide positive electrode, a carbon material negative electrode, a carbonate electrolyte dissolved with a certain concentration of lithium hexafluorophosphate, and a diaphragm. On the surface of the diaphragm, inorganic powders (alumina, boehmite) are coated as ceramic coatings, and the inorganic powders contain transition metal ion impurities. These ions will dissolve, especially when the battery is stored or circulated under extreme conditions such as high voltage and high temperature. The dissolved transition metals cause the battery capacity to decay sharply and even cause safety problems.

[0003] In the existing process, water washing is mainly used to remove impurity ions in inorganic powders. For example, Chinese patent CN108565379 B discloses a lithium battery separator and its preparation method, wherein the preparation method includes: 1) adding an aromatic polymer and a ceramic powder to a solvent to dissolve to obtain an aromatic polymer slurry; 2) coating the aromatic polymer slurry on the surface of a lithium battery base film; 3) washing the structure obtained in step 2) in a constant temperature water bath, and then drying to obtain a lithium battery separator. However, the above-mentioned water washing method can only clean the ions on the surface of the powder particles, and the internal ions will gradually migrate outward during use.

[0004] Chinese patent application CN 106186008 A discloses a boehmite for lithium battery separator ceramic coating and a hydrothermal preparation method thereof, wherein the purity of the boehmite is up to 99.95%; Chinese patent CN 114538488 A discloses a preparation method of high-purity boehmite for lithium battery separator, wherein the purity of the boehmite can reach 99.99%, but those skilled in the art understand that the higher the purity level, the more difficult it is to purify it, which not only makes the process more complicated, but also greatly increases the cost, making it difficult to mass produce on a large scale. Summary of the invention

[0005] The object of the present invention is to provide a composite powder for a battery separator, wherein the ion dissolution amount of the powder is small, and the battery separator prepared from the powder has good wettability with the electrolyte.

[0006] The present invention achieves the above technical objectives through the following technical means.

[0007] A composite powder for a battery separator comprises an inorganic powder and a polymer layer coated on the surface of the inorganic powder particles, wherein the inorganic powder is selected from one or more of alumina and boehmite, and the polymer layer comprises one or more of polymethyl methacrylate (PMMA), silicone polymer, polyphenylene ether (PPO), and polyethylene naphthalate (PEN), and the mass of the polymer layer accounts for 1-10wt% of the mass of the composite powder.

[0008] Another object of the present invention is to provide a method for preparing a composite powder for a battery separator ceramic coating.

[0009] The present invention achieves the above technical objectives through the following technical means.

[0010] A method for preparing a composite powder for a battery separator, selected from one of the following preparation methods: Method 1: Step S1: heating and dissolving the dispersant in water; Step S2: uniformly mixing the inorganic powder, methyl methacrylate, crosslinking agent, initiator and dispersant according to proportion; Step S3: pour the mixed solution in step S2 into the dispersant solution in step S1, stir, heat in a water bath, control the temperature, react at 80-85°C for 1-2 hours, react at 85-90°C for 1-2 hours, and react at 90-95°C for 1-2 hours; Method 2: Step A: weighing a buffer pair according to a certain mass ratio, diluting the buffer pair with deionized water to a fixed pH to obtain a buffer solution; Step B: Take an appropriate amount of buffer solution, add inorganic powder and stir to disperse, add silane to the buffer solution, and perform hydrolysis reaction at a certain temperature and stirring speed; Step C: raising the temperature to carry out polycondensation reaction; Step D: Centrifugation, washing and drying to obtain composite powder.

[0011] Furthermore, in the method one, the weight ratio of the inorganic powder, dispersant, and methyl methacrylate in step S2 is: 400: (1-5): (10-40): (1-2): (1.5-2): 1.

[0012] Furthermore, in the method 2, the pH in step A is 3-5 or 8-12, the buffer pair is one of a weak acid and its salt, a weak base and its salt, an acid salt of a polybasic weak acid and its corresponding secondary salt, and the mass ratio of the buffer pair is (1-2):(1-160).

[0013] Furthermore, in the method 2, the mass ratio of the buffer solution, the inorganic powder and the silane in step B is (200-2500): (250-1500): (18-25); the silane is phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, acryltrimethoxysilane, acryltriethoxysilane, chloropropyltriethoxysilane, mercaptopropyltrimethoxysilane. , mercaptopropyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, tetraethoxysilane or at least one of tetramethoxysilane, preferably at least one of methyltrimethoxysilane, phenyltrimethoxysilane and ethyltriethoxysilane; the hydrolysis temperature is 20-40°C; the hydrolysis reaction time is 1-4h; the hydrolysis stirring speed is 100-600r / min.

[0014] Furthermore, in the method 2, the temperature of the polycondensation reaction in step C is 50-70°C; the polycondensation reaction time is 1-10h; and the polycondensation stirring speed is 100-600r / min.

[0015] Furthermore, in the method 2, the centrifugal speed in step D is 2000-10000 r / min; the washing solvent is an alcohol solvent; the drying temperature is 50-100° C.; and the drying time is 4-12 h.

[0016] Another object of the present invention is to provide a battery separator.

[0017] The present invention achieves the above technical objectives through the following technical means.

[0018] A battery separator comprises a base film and a ceramic coating formed on at least one side of the base film, wherein the ceramic coating comprises the composite powder for battery separators or the composite powder for battery separators prepared by the preparation method.

[0019] Another object of the present invention is to provide a battery.

[0020] The present invention achieves the above technical objectives through the following technical means.

[0021] A battery comprises the battery separator mentioned above.

[0022] Another object of the present invention is to provide an electrochemical device.

[0023] The present invention achieves the above technical objectives through the following technical means.

[0024] An electrochemical device comprises the battery mentioned above. Beneficial Effects

[0025] The present invention can achieve the following technical effects by coating a polymer layer on the surface of aluminum oxide and boehmite to form a composite powder, and applying the composite powder to a battery separator.

[0026] 1. Compared with conventional uncoated alumina and boehmite, the composite powder of the present invention has less precipitation of transition metal ions.

[0027] 2. The battery separator of the present invention has better wettability with electrolyte than the conventional separator coated with alumina or boehmite.

[0028] 3. The electrochemical device of the present invention has reduced battery capacity attenuation compared with lithium batteries using conventional separators coated with alumina or boehmite. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Example 1 Alumina SEM image.

[0030] Figure 2 SEM image of the composite powder of Example 1. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood. The present invention will be further described below in conjunction with the drawings and specific embodiments.

[0032] The reagents used in the following examples are all commercially available. Example 1

[0033] Take 2kg of gelatin (dispersant), dissolve it in water and heat it to dissolve it in water, add 400KG of alumina (D50 1 micron), and pour it into the reactor while hot; then take 40kg of methyl methacrylate (monomer), 1kg of divinylbenzene (cross-linking agent), 1.5kg of azobisisobutyronitrile (initiator), and 1kg of PVP (co-dispersant), put them together and stir them evenly, then pour them into the above-mentioned reactor, then install the agitator, heating furnace and condenser, start water bath heating, and control the temperature; react at 80℃ for 1 hour, 85℃ for 1 hour, and 90℃ for 2 hours; stop heating, the reaction is over, wash with ethanol and centrifuge, the centrifugal speed is 8000r / min, and dry at 80℃ for 8h to obtain a PMMA-coated composite powder with a particle size D50 of 1.3 microns. Example 2

[0034] Take 1kg of gelatin (dispersant), dissolve it in water and heat it to dissolve it in water, add 400KG of alumina (D50 1 micron), and pour it into the reactor while hot; then take 20kg of methyl methacrylate (monomer), 2kg of divinylbenzene (cross-linking agent), 2kg of azobisisobutyronitrile (initiator), and 1kg of PVP (co-dispersant), put them together and stir them evenly, then pour them into the above-mentioned reactor, then install the agitator, heating furnace and condenser, start water bath heating, and control the temperature; react at 85℃ for 1 hour, 90℃ for 1 hour, and 90℃ for 2 hours; stop heating, the reaction is over, wash with ethanol and centrifuge, the centrifugal speed is 8000r / min, and dry at 80℃ for 8h to obtain a PMMA-coated composite powder with a particle size D50 of 1.2 microns. Example 3

[0035] Take 1kg of gelatin (dispersant), dissolve it in water and heat it to dissolve it in water, add 400KG of boehmite (D50 0.9 micron), and pour it into the reactor while hot; then take 20kg of methyl methacrylate (monomer), 2kg of divinylbenzene (cross-linking agent), 2kg of azobisisobutyronitrile (initiator), and 1kg of PVP (co-dispersant), put them together and stir them evenly, then pour them into the above-mentioned reactor, then install the agitator, heating furnace and condenser, start water bath heating, and control the temperature; react at 85℃ for 1 hour, 90℃ for 1 hour, and 90℃ for 2 hours; stop heating, the reaction is over, wash with ethanol and centrifuge, the centrifugal speed is 8000r / min, and dry at 80℃ for 8h to obtain a PMMA-coated composite powder with a particle size D50 of 1.1 microns. Example 4

[0036] (1) Weigh 80 parts of disodium hydrogen phosphate and 1 part of potassium dihydrogen phosphate and dilute them with deionized water to obtain a buffer solution with a pH of 10.

[0037] (2) Take 240 parts of the buffer solution from (1), add 300 parts of aluminum oxide (D50 0.5 μm), add 24 parts of methyltrimethoxysilane to the buffer solution, and hydrolyze at 30°C for 2 hours with a stirring speed of 200 r / min.

[0038] (3) Polycondensation was carried out at 50°C for 4 h with a stirring speed of 200 r / min.

[0039] (4) Wash with ethanol and centrifuge at a centrifugal speed of 8000 r / min, and dry at 80°C for 8 h to obtain a composite powder coated with a silicone polymer with a particle size D50 of 0.7 μm. Example 5

[0040] (1) Weigh 30 parts of ammonia water and 5 parts of ammonium chloride and dilute them with deionized water to obtain a buffer solution with a pH of 10.

[0041] (2) Take 250 parts of the buffer solution from (1), add 400 parts of aluminum oxide (D50 0.5 μm) and add 25 parts of ethyltriethoxysilane to the buffer solution, hydrolyze at 40°C for 2 hours, and stir at 300 r / min.

[0042] (3) Polycondense at 70°C for 2 h with a stirring speed of 300 r / min.

[0043] (4) washing with ethanol and centrifuging at a centrifugal speed of 8000 r / min, and drying at 80° C. for 8 h to obtain a composite powder coated with an organic silicon polymer with a particle size D50 of 0.6 μm. Example 6

[0044] (1) Weigh 30 parts of ammonia water and 5 parts of ammonium chloride and dilute them with deionized water to obtain a buffer solution with a pH of 10.

[0045] (2) Take 250 parts of the buffer solution from (1), add 400 parts of boehmite (D50 0.5 μm) and add 25 parts of ethyltriethoxysilane to the buffer solution. Hydrolyze at 40°C for 2 hours with a stirring speed of 300 r / min.

[0046] (3) Polycondense at 70°C for 2 h with a stirring speed of 300 r / min.

[0047] (4) washing with ethanol and centrifuging at a centrifugal speed of 8000 r / min, and drying at 80° C. for 8 h to obtain a composite powder coated with an organic silicon polymer with a particle size D50 of 0.6 μm.

[0048] Application Example 1-6 (Preparation of Diaphragm) A coating slurry containing the composite powder obtained in Examples 1-6 was prepared, with a solid content of 30%, wherein the solid component included the composite powder and, by weight of the composite powder, 5wt% of a binder (butyl polyacrylate), 0.2wt% of a wetting agent (sodium lauryl sulfate), and 1.2wt% of a thickener (sodium carboxymethyl cellulose). The slurry was applied to both sides of a 5-micron thick diaphragm, with a coating thickness of 1.5 microns, as Application Examples 1-6.

[0049] Comparative Examples 1-6 A coating slurry containing an inorganic powder (alumina or boehmite) of the same particle size as the composite powder of Examples 1-6 was prepared, with a solid content of 30%, wherein the solid component included the inorganic powder and, by weight of the inorganic powder, 5wt% of a binder (butyl polyacrylate), 0.2wt% of a wetting agent (sodium lauryl sulfate), and 1.2wt% of a thickener (sodium carboxymethyl cellulose). The slurry was coated on both sides of a 5-micron thick diaphragm, with a coating thickness of 1.5 microns, as Comparative Examples 1-6.

[0050] Table 1 Ionic conductivity test of composite powder and inorganic powder in Example

[0051] Method: Add the powder into pure water, stir and place, and test the conductivity of the water with a conductivity meter.

[0052] Table 2 tests the contact angles of carbonate electrolytes of lithium hexafluorophosphate salt on the application example and comparative example diaphragms.

[0053]

[0054] A battery was assembled with activated carbon as the positive electrode, lithium titanate as the negative electrode, a carbonate electrolyte of lithium hexafluorophosphate salt, and the separators of the embodiment and the comparative example, and the capacity retention rate was tested.

[0055] Diaphragm thermal shrinkage test standard: Based on GB / T36363-2018.

[0056] Test conditions: Heat shrinkage: 105℃ / 1 hour.

[0057] It can be seen from Table 1 that the ionic conductivity of the aqueous solution of the composite powder of the embodiment changes less with the extension of the storage time than that of the corresponding inorganic powder. The possible reason is that after the inorganic powder is coated, it is difficult for the transition metal ions to migrate into the water.

[0058] It can be seen from Table 2 that the contact angle of the diaphragm coated with the composite powder is small, and the smaller the contact angle, the faster the wetting speed and the better the wettability. At the same time, from the capacity retention rate of the battery after 2000 charge and discharge cycles, it can be seen that the battery capacity decay of the diaphragm coated with the composite powder is slowed down.

[0059] The series of detailed descriptions listed above are only specific descriptions of feasible implementation modes of the present invention, but the present invention is not limited to the above-mentioned implementation modes. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A composite powder for battery separator, characterized in that: The composite material comprises an inorganic powder and a polymer layer coated on the surface of the inorganic powder particles, wherein the inorganic powder is selected from one or more of alumina and boehmite, and the polymer layer comprises one or more of polymethyl methacrylate (PMMA), silicone polymer, polyphenylene ether (PPO), and polyethylene naphthalate (PEN), and the mass of the polymer layer accounts for 1-10wt% of the mass of the composite powder.

2. A method for preparing a composite powder for a battery separator according to claim 1, characterized in that: Select one of the following preparation methods: Method 1: Step S1: heating and dissolving the dispersant in water; Step S2: uniformly mixing the inorganic powder, methyl methacrylate, crosslinking agent, initiator and dispersant according to proportion; Step S3: pour the mixed solution in step S2 into the dispersant solution in step S1, stir, heat in a water bath, control the temperature, react at 80-85°C for 1-2 hours, react at 85-90°C for 1-2 hours, and react at 90-95°C for 1-2 hours; Method 2: Step A: weighing a buffer pair according to a certain mass ratio, diluting the buffer pair with deionized water to a fixed pH to obtain a buffer solution; Step B: Take an appropriate amount of buffer solution, add inorganic powder and stir to disperse, add silane to the buffer solution, and perform hydrolysis reaction at a certain temperature and stirring speed; Step C: raising the temperature to carry out polycondensation reaction; Step D: Centrifugation, washing and drying to obtain composite powder.

3. The method for preparing a composite powder for a battery separator according to claim 2, characterized in that: In the method 1, the weight ratio of the inorganic powder, dispersant and methyl methacrylate in step S2 is: 400: (1-5): (10-40): (1-2): (1.5-2):

1.

4. The method for preparing a composite powder for a battery separator according to claim 2, characterized in that: In the method 2, the pH in step A is 3-5 or 8-12, the buffer pair is one of a weak acid and its salt, a weak base and its salt, an acid salt of a polybasic weak acid and its corresponding secondary salt, and the mass ratio of the buffer pair is (1-2):(1-160).

5. The method for preparing a composite powder for a battery separator according to claim 2, characterized in that: In the method 2, the mass ratio of the buffer solution, the inorganic powder and the silane in step B is (200-2500): (250-1500): (18-25); the silane is phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, acryltrimethoxysilane, acryltriethoxysilane, chloropropyltriethoxysilane, mercaptopropyltrimethoxysilane, mercaptopropyl At least one of triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, tetraethoxysilane or tetramethoxysilane, preferably at least one of methyltrimethoxysilane, phenyltrimethoxysilane and ethyltriethoxysilane; the hydrolysis temperature is 20-40°C; the hydrolysis reaction time is 1-4h; the hydrolysis stirring speed is 100-600r / min.

6. The method for preparing a composite powder for a battery separator according to claim 2, characterized in that: In the method 2, the temperature of the polycondensation reaction in step C is 50-70° C.; the polycondensation reaction time is 1-10 h; and the polycondensation stirring speed is 100-600 r / min.

7. The method for preparing a composite powder for a battery separator according to claim 2, characterized in that: In the method 2, the centrifugal speed in step D is 2000-10000 r / min; the washing solvent is an alcohol solvent; the drying temperature is 50-100° C.; and the drying time is 4-12 hours.

8. A battery separator, characterized in that: It comprises a base film and a ceramic coating formed on at least one side of the base film, wherein the ceramic coating comprises the composite powder for battery separator according to claim 1 or the composite powder for battery separator prepared by the preparation method according to any one of claims 2-7.

9. A battery, characterized in that: The battery separator according to claim 8 is included.

10. An electrochemical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Boehmite used for lithium battery diaphragm coating layer and hydro-thermal preparation method thereof

    CN106186008A

  • A lithium battery separator and its preparation method

    CN108565379B

  • Preparation method of high-purity boehmite for lithium battery diaphragm

    CN114538488A

  • Coating slurry, lithium-ion battery separator and preparation methods of coating slurry and lithium-ion battery separator

    CN106519872A

  • High-temperature-resistant polymer modified ceramic diaphragm and application thereof

    CN108666511A